Burnout syndrome and lifestyles in teachers of the health faculty of a private university in Peru in times of pandemic - Valverde Asencios, Merlinda (2021)
Objective: To determine the relationship between Burnout Syndrome and lifestyles in teachers ofthe health faculty of a private university in times of pandemic. Methodology: Quantitative approach,non-experimental design, correlational type and cross-sectional. The sample was non-probabilistic forconvenience, obtaining a total of 120 participants. The instruments used for data collection were theMBI version Ed created by Maslach, Jackson and Schwab in 1986 adapted by Fernández (2002) andthe FANTASTIC lifestyle questionnaire created by Douglas et al. (1984) adapted by Villar et al. (2016).Results: There is an inverse and statistically significant correlation between lifestyle and burnoutsyndrome demonstrated by a p <.001 and a rho = -.461; in terms of descriptive results; 69.6% ofthe health faculty teachers present a medium level of Burnout syndrome, 42% present an adequatelifestyle. Conclusion: There is an inverse relationship between the study variables, which shows thata healthy lifestyle can function as a protector for the mental health of teachers.